TCH-020 Improving Efficiency in Elastomeric Pump Filling Using DIANA ONCO PLUS, a Semi-Automated Compounding Device. (12th March 2013) - Castell, P; Ausina, MJ; Sanz, R; Palomo-Jimenez, PI; Lopez-Briz, E; Ramirez, P; Ceita, M; Chilet, A; Estela, A; Poveda-Andres, JL
Abstract : Background: La Fe Universitario y Politécnico Hospital is a tertiary-care hospital with approximately 1000 beds serving a population of 210, 000 people. The pharmacy department owns 4 vertical laminar flow hoods where more than 35, 000 chemotherapy treatments, including the filling of 800 elastomeric pumps, are prepared per year. Purpose: To compare both the time spent and the accuracy in the filling of elastomeric pumps (EPs) with fluorouracil by two different methods: DIANA ONCO-PLUS, a semi-automated compounding system (ICU Medical Europe), and the normal manual method used in the hospital's Chemotherapy Unit (CU). The secondary endpoint was to assess user satisfaction with the two methods. Materials and Methods: For 4 consecutive weeks, EPs were filled by trained nurses two days per week. The first day DIANA ONCO-PLUS was used and the second day the EPs were filled manually. To avoid bias, every week a different nurse filled the EPs using both methods. Filling time was measured by a different nurse using a conventional chronograph and the accuracy was evaluated by weight of EP (before and after filling). Nurses' satisfaction was assessed by a questionnaire. Results: The filling of sixty-five EPs was evaluated. The filling mean time was 4.25 min with the manual method and 3.84 min with DIANA ONCO-PLUS (p = 0.008). If purge is considered, the mean time was 6.63 min and 5.52 min respectively (p < 0.001). The mean relative error in the filling was 0.735% in manual method and 0.314% in DIANA method (p = 0.006) without any clinical relevance. There was no user-related variability. Nurses were very satisfied using DIANA for filling EP. They considered DIANA more comfortable and safe. Conclusions: DIANA ONCO-PLUS is a more efficient and accurate method to fill EPs than the manual method. The differences found were user-independent. Acknowledgements: The authors thank the Pharmacy Department of HUP La Fe, Nagore Castro, Loreto Gómez (Hospira PFH SL) and Roberto Zambrano (ICU Medical) for their collaboration in this study. No conflict of interest.